Dopamine drives binge‐like consumption of a palatable food in experimental Parkinsonism - Mineo, Désirée; Cacace, Fabrizio; Mancini, Maria; Vannelli, Anna; Campanelli, Federica; Natale, Giuseppina; Marino, Gioia; Cardinale, Antonella; Calabresi, Paolo; Picconi, Barbara; Ghiglieri, Veronica (Movement disorders, 2019)
Background Prolonged dopaminergic replacement therapy in PD results in pulsatile dopamine receptors stimulation in both dorsal and ventral striatum causing wearing off, motor fluctuations, and nonmotor side effects such as behavioral addictions. Among impulse control disorders, binge eating can be easily modeled in laboratory animals. Objectives We hypothesize that manipulation of dopamine levels in a 6‐hydroxydopamine–lesioned rats, as a model of PD characterized by a different extent of dopamine denervation between dorsal and ventral striatum, would influence both synaptic plasticity of the nucleus accumbens and binge‐like eating behavior. Methods Food preference, food intake, and weight gain were monitored in sham‐operated and unilaterally lesioned rats, subjected to a modified version of Corwin's limited access protocol, modelling binge eating disorder. Electrophysiological properties and long‐term potentiation of GABAergic spiny projection neurons of the nucleus accumbens core were studied through ex vivo intracellular and patch‐clamp recordings from corticostriatal slices of naïve and l‐dopa–treated rats. Results Sham‐operated animals with intact nucleus accumbens core plasticity reliably developed food‐addiction–like behavior when exposed to intermittent access to a highly palatable food. In contrast, parkinsonian rats were unresponsive to such restriction regimens, and also plasticity was lost in ventral spiny neurons. Chronic l‐dopa reestablished long‐term potentiation and compulsive eating, but with a different temporal dynamic that follows that of drug administration. Conclusions Our data indicate that endogenous and exogenous dopamine drive binge‐like consumption of a palatable food in healthy and parkinsonian rats with distinct temporal dynamics, providing new insights into the complexity of l‐dopa effects on the mesolimbic dopaminergic system. © 2019 International Parkinson and Movement Disorder Society